Implementasi Metode Takror untuk Meningkatkan Retensi Hafalan Siswa pada Program Tahfidzul Qur’an di Madrasah Aliyah Raudlatul Ulum Putri - Zuyyina Linda Sari; Abdurrohim Abdurrohim (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Memorizing the Qur’an is not just about the ability to store verses in memory, but also about how to maintain those memorized verses so that they remain strong and enduring in the long term. At MA Raudlatul Ulum Putri, the tahfidz activity is an essential part of the daily routine of the female students, and the method of takror (repetition) is implemented as the main strategy to support the sustainability of their memorization. This study aims to describe how the takror method is implemented in the Qur’an Memorization program and its impact on students' retention of memorized verses. Using a descriptive qualitative approach, data was collected through observations, interviews with the tahfidz teachers, and several students. The findings show that the implementation of takror is carried out in three stages: planning, implementation, and evaluation. All activities are organized by one teacher responsible for tahfidz, and are conducted in a special class that accommodates takror time separately from general lessons. This takror method not only strengthens the students' memory of the verses they have memorized but also fosters a sense of responsibility, discipline, and provides tranquility and satisfaction for the students in the process of memorizing the Qur’an).